The Coming of Consumer Society - Kaur, Kulwinder, (Brill | Manohar Publishers & Distributors, 2016)
The present volume adds momentum to the ongoing discourse on consumerism in India and offers a fresh perspective by arguing that India is not just a consumer market but a consumer society in the making. There is no consensus on the birth, place and context of a consumer society amongst historians. And for scholars of contemporary social life, consumer societies, till recently were held to be akin to societies in the late stage of capitalism or those having completed their transition from feudalism to post-industrialism. However, given the processes of globalization and liberalization of new global economic order, consumerism as an ideology, a world view and a practice is fast 'coming of age' in other societies across the globe. Hence, the earlier intellectual lexicon stands replaced by a new consumer epistemology signalling the coming of new consumer societies in hitherto unimagined locales such as India. The varied essays in the volume develop the themes of consumption, brands, representation, and identity construction in some new settings - so far unexplored in the Indian context - for instance ethnic brands such as Fabindia; tribal art in new digitized forms; fashion; and so on. The strength of the book lies in traversing not just fresh sites and objects of consumer desire, but also in bringing together a host of multidisciplinary and theoretical perspectives such as Marxism, feminism, postmodernism, and post-colonialism. The book would be of interest to students and researchers of sociology, anthropology, politics, cultural studies and media studies.